Talking about living and dying with the oldest old: public involvement in a study on end of life care in care homes - Goodman Claire; Mathie Elspeth; Cowe Marion; Mendoza Alex; Westwood Daphne; Munday Diane; Wilson Patricia M; Crang Clare; Froggatt Katherine; Iliffe Steve; Manthorpe Jill; Gage Heather; et al. (BMC Palliative Care, 2011)
Abstract Background Public involvement in research on sensitive subjects, such as death and dying, can help to ensure that questions are framed to reflect the interests of their peers, develop a shared understanding of issues raised, and moderate the often unequal power relationship between researcher and participant. This paper describes the contribution and impact of older members of a Public Involvement in Research group (PIRg) to a study on living and dying in care homes. Methods A longitudinal study, with a mixed method approach, its aims were to capture key experiences, events and change over one year, of older people resident in participating care homes in the East of England. Residents were interviewed up to three times and their case notes were reviewed four times over the year. Interviews were semi structured, and recorded. Four members of a Public Involvement in Research group (PIRg) contributed to preliminary discussions about the research and three were involved with many of the subsequent stages of the research process including the facilitation of discussion groups with residents. Results There were three areas where the involvement of the Public Involvement in Research group (PIRg) positively influenced the study process. These were recruitment, governance and safeguarding, and in collaboration with the residents in the care homes, the discussion and interpretation of emergent findings. PIRg members were of similar age to the residents and their involvement provided different and often more reflective insights of the significance of the findings for the participants. There were examples where decision making about the range of PIRg participation was not always negotiable, and this raised issues about power relationships within the team. Nevertheless, PIRg members expressed personal benefit and satisfaction through participating in the research and a commitment to continue to support research with this older age group. Conclusions The contribution of the PIRg supported a successful recruitment process that exceeded response rates of other studies in care homes. It safeguarded residents during the conduct of research on a sensitive topic and helped in validating the interview data gathered by the researchers through the discussion groups facilitated by the PIRg. There were power differentials that persisted and affected PIRg participation. The study has showed the value of developing job descriptions and a more formal means of setting out respective expectations. Future research may wish to elicit the views of focal participants in such studies about the mediation of research by public involvement in research.